Hirschman’s Choice: Exiles and Obligations of an anti-Fascist - Jeremy Adelman (Transatlantica)
This essay uses the life history of Albert O. Hirschman,1 especially the years of his active political engagements that preceded his intellectual career, to explore the “micro-history” of choices about whether to stay and fight or back and flee. It also considers some of Hirschman’s own thinking about action—and the choices between exercising voice, loyalty, or defection, the bases of his influential book, Exit, Voice, and Loyalty. Finally, it explores the ever-complicated connections between personal experience and theoretical reflection.